If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y(y) + -5y + 6 + -15y(y) + -5y + 6 = 0 Multiply y * y 7y2 + -5y + 6 + -15y(y) + -5y + 6 = 0 Multiply y * y 7y2 + -5y + 6 + -15y2 + -5y + 6 = 0 Reorder the terms: 6 + 6 + -5y + -5y + 7y2 + -15y2 = 0 Combine like terms: 6 + 6 = 12 12 + -5y + -5y + 7y2 + -15y2 = 0 Combine like terms: -5y + -5y = -10y 12 + -10y + 7y2 + -15y2 = 0 Combine like terms: 7y2 + -15y2 = -8y2 12 + -10y + -8y2 = 0 Solving 12 + -10y + -8y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '2'. 2(6 + -5y + -4y2) = 0 Factor a trinomial. 2((3 + -4y)(2 + y)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(3 + -4y)' equal to zero and attempt to solve: Simplifying 3 + -4y = 0 Solving 3 + -4y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4y = 0 + -3 -4y = 0 + -3 Combine like terms: 0 + -3 = -3 -4y = -3 Divide each side by '-4'. y = 0.75 Simplifying y = 0.75Subproblem 2
Set the factor '(2 + y)' equal to zero and attempt to solve: Simplifying 2 + y = 0 Solving 2 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Simplifying y = -2Solution
y = {0.75, -2}
| 9x+14y+20+8x-13y-18= | | x^2-2x-22.4=0 | | (3x^2+8x)(25x^2-5x-2)=0 | | 6x(x+6y+z)= | | z^2-4z-12= | | 25r^2+60rg+36g^2=0 | | -3(8x-3y+4)= | | 8x^2y-4xy^2+5xy=0 | | 12=5k-4 | | x^2-31x+300=0 | | 5x+35=95 | | y=.20x*8+35 | | (12)-(y)=15 | | (10x-6-3p)= | | 2v-10v-12=(v-3)(v-3) | | y=.2x*8+35 | | 9.5+27= | | [x+2]=5 | | 0.2(60)+0.5x=0.1(60+x) | | a^3-3a^2+2a+9=0 | | 295=r/51 | | m/98=43 | | 64382=39y | | 210x=4119 | | 6w^2-37w-35=0 | | 81x^2y^-2/3 | | 3x+1x= | | 56b^2+b+1=0 | | 10/11x=120 | | 7d^2-22d+16=0 | | x(60-x)=0 | | x+3.3=7.7 |